2017
DOI: 10.1038/nature24627
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the human MHC-I peptide-loading complex

Abstract: The peptide-loading complex (PLC) is a transient, multisubunit membrane complex in the endoplasmic reticulum that is essential for establishing a hierarchical immune response. The PLC coordinates peptide translocation into the endoplasmic reticulum with loading and editing of major histocompatibility complex class I (MHC-I) molecules. After final proofreading in the PLC, stable peptide-MHC-I complexes are released to the cell surface to evoke a T-cell response against infected or malignant cells. Sampling of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
298
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 315 publications
(321 citation statements)
references
References 59 publications
13
298
0
1
Order By: Relevance
“…The discovery that TAPBPR can function as a peptide exchange catalyst outside the peptideloading complex and can maintain empty MHC-I molecules in a peptide-receptive conformation has opened a new window to study the peptide loading process in a range of detailed functional and mechanistic studies (4,12,13). Structural insights into static snapshots of MHC-I/chaperone complexes have been gleaned by X-ray crystallography (14,15) and cryoEM (16). However, MHC-I molecules are inherently dynamic at multiple sites (17,18) and transitions between different "open" and "closed" conformations enable peptide loading, as shown by molecular dynamics (MD) simulation (19,20) and kinetic modeling (21).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that TAPBPR can function as a peptide exchange catalyst outside the peptideloading complex and can maintain empty MHC-I molecules in a peptide-receptive conformation has opened a new window to study the peptide loading process in a range of detailed functional and mechanistic studies (4,12,13). Structural insights into static snapshots of MHC-I/chaperone complexes have been gleaned by X-ray crystallography (14,15) and cryoEM (16). However, MHC-I molecules are inherently dynamic at multiple sites (17,18) and transitions between different "open" and "closed" conformations enable peptide loading, as shown by molecular dynamics (MD) simulation (19,20) and kinetic modeling (21).…”
Section: Introductionmentioning
confidence: 99%
“…Both in vitro kinetic analyses and in cellulo inhibitor and siRNA experiments demonstrated that ERAP1 generates and stabilizes the minimal gp100 209-217 epitope. This is in contrast to the MART-1 [26][27][28][29][30][31][32][33][34][35] (melanoma antigen recognized by T cells) epitope being destroyed by ERAP1 [24]. ERAP1 has been shown to be constitutively expressed in tumor cells, even in the absence of IFN-γ [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…An exciting finding here is how the Kir6.2 N-terminus can act as a plug or handle to regulate channel gating and assembly by inserting itself into the ABC core central cavity formed by the two TM bundles. The exploitation of this structural space is akin to the mechanism by which viral peptide ICP47 enables immuneevasion of the pathogens (Blees et al, 2017;Oldham et al, 2016;Parcej and Tampe, 2010). In this case, ICP47 secreted by viruses such as Herpes simplex virus and Cytomegalovirus inserts into the inner vestibule formed by the ABC peptide transporters TAP-1 and TAP-2 (transporter associated with antigen processing) (Blees et al, 2017;Oldham et al, 2016), thus preventing the transport of cytosolic peptides into the ER for MHC complex loading and immune surveillance.…”
Section: Discussionmentioning
confidence: 99%